Ethanol concentration induces production of 3, 4-dihydroxyphenylacetic acid and homovanillic acid in mouse brain through activation of monoamine oxidase pathway. (21st June 2022) - Jamal, Mostofa; Ito, Asuka; Miki, Takanori; Suzuki, Shingo; Ohta, Ken-Ichi; Kinoshita, Hiroshi
Graphical abstract: Highlights: EtOH 3.0 g/kg dose increased the levels of DOPAC and HVA and decreased the levels of 3-MT. Clorgyline alone increased 3-MT and decreased DOPAC and HVA levels. Tolcapone alone increased DOPAC and decreased 3-MT and HVA levels. Combination of EtOH with clorgyline or tolcapone further decreased 3-MT and increased DOPAC and HVA levels. Abstract: First, we aimed to investigate ex vivo the effects of ethanol (EtOH) on levels of norepinephrine (NE), dopamine (DA), serotonin (5-HT), and their metabolites in the frontal cortex, hippocampus, and striatum of Aldh2 -knockout ( Aldh2 -KO) and wild-type (WT) mice. Animals were treated intraperitoneally with saline (control) or EtOH (1.0, 2.0, or 3.0 g/kg). Brain samples were collected 60 and 120 min after EtOH injection, and monoamines and their metabolites were measured by HPLC-ECD. We found in both WT and Aldh2 -KO mice that 3.0 g/kg EtOH increased the levels of 3, 4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA) and decreased the level of 3-methoxytyramine (3-MT). A 2.0 g / kg dose of EtOH also increased HVA, but there was not a consistent effect within the brain regions of Aldh2 -KO and WT mice. There were inconsistent findings of genotype differences in the levels of DA, 5-HT, and their metabolites in the brain regions tested. None of the EtOH doses altered NE, DA, 5-HT, or 5-hydroxyindoleacetic acid contents in any of the brain regions studied. Second, we tested whether EtOH-induced increases in DOPAC and HVA are mediated by increased monoamine oxidase (MAO) or catechol-O-methyltransferase (COMT) activity. To test this, we used the MAO blocker clorgyline (2.0 and 4.0 mg/kg) and the COMT blocker tolcapone (15 and 30 mg/kg) alone or in combination with EtOH (3.0 g/kg). Clorgyline alone increased 3-MT and decreased DOPAC and HVA levels, whereas tolcapone alone increased DOPAC and decreased 3-MT and HVA levels. Surprisingly, the combination of EtOH with clorgyline (4.0 mg/kg) or tolcapone (30 mg/kg) further decreased 3-MT and increased DOPAC and HVA levels, an effect that reversed the inhibitor-induced decreases in HVA. These results suggest that a high concentration of EtOH can accelerate DA metabolism, as evidenced by the increase in DOPAC and HVA, and this effect is likely a consequence of increased degradation of DA by MAO.